1983
DOI: 10.1136/bmj.287.6403.1417
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric morbidity in patients with alcoholic liver disease.

Abstract: 1417composition in relation to fall in blood pressure with a note on measurement of angiotensin II during converting enzyme inhibition. Br HeartJ7

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
30
0

Year Published

1984
1984
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 19 publications
1
30
0
Order By: Relevance
“…14,15,27 Other studies supported an association between HCV infection and depression. These studies found that patients with HCV infection were more likely to have psychiatric disorders; depression was the most frequent and clinically important diagnosis.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…14,15,27 Other studies supported an association between HCV infection and depression. These studies found that patients with HCV infection were more likely to have psychiatric disorders; depression was the most frequent and clinically important diagnosis.…”
Section: Discussionmentioning
confidence: 88%
“…In early studies, the morbidity of mood and anxiety disorders was increased in patients with alcoholic cirrhosis compared with cirrhoses of other causes, using the Schedule for Affective Disorders and Schizophrenia and Research Diagnostic Criteria. 14,15 EwusiMensah et al 14 found that two thirds of in-patients with alcoholic liver disease had diagnosable psychiatric disorders compared with one third of a control group of patients with nonalcoholic liver disease. Another study found that three quarters of patients with alcoholic liver disease were affected by psychiatric disorders compared with only a quarter of nonalcoholic patients with liver disease.…”
mentioning
confidence: 99%
“…4 Of 2 studies evaluating liver transplant candidates/recipients, the first (N = 73) identified 17% with symptoms of depression and 33% with symptoms of anxiety during pretransplantation assessment 5 ; whereas the second (N = 71) identified 66% with a current or past psychiatric illness, though none with psychotic spectrum disorders, such as schizophrenia and schizoaffective disorders. 6 A study evaluating heart transplant recipients indicated that "depression" (all forms) correlated positively with heart transplantation and with likelihood of posttransplant intervention needs. 7 In our review of the literature, no information on pre-existing mental illness rates was found for intestinal, lung, bone marrow, or pancreas transplants, although much was available about posttransplant mental health symptom development (regardless of transplant type).…”
mentioning
confidence: 99%
“…Patients were equally as likely to have developed depression before using alcohol excessively as they were afterwards. 43 Risk factors for alcohol recidivism after OLT have been found to include pre-operative depression and level of alcohol consumption, 44 with the evidence regarding the extent to which duration of pre-transplant abstinence contributes being contradictory.…”
Section: Hepatitis Bmentioning
confidence: 99%